Avaliação do tempo de dreno de sucção em pacientes submetidos à artrodese lombar: estudo prospectivo randomizado (Brazilian Journal of Health Research, 2019)
Evaluation of the suction drain time in patients undergoing lumbar arthrodesis: prospective randomized study